2017
DOI: 10.3389/fnmol.2017.00221
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Concentrations of Amyloid Beta Regulate Recycling of Synaptic Vesicles via Alpha7 Acetylcholine Receptor and CDK5/Calcineurin Signaling

Abstract: Despite the central role of amyloid β (Aβ) peptide in the etiopathogenesis of Alzheimer’s disease (AD), its physiological function in healthy brain is still debated. It is well established that elevated levels of Aβ induce synaptic depression and dismantling, connected with neurotoxicity and neuronal loss. Growing evidence suggests a positive regulatory effect of Aβ on synaptic function and cognition; however the exact cellular and molecular correlates are still unclear. In this work, we tested the effect of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 48 publications
12
73
0
Order By: Relevance
“…The enhancement of PTP by APPsa, as observed in our study, is consistent with previous studies that reported increased Ca 2+ influx in synaptoneurosomes and a7-nAChRs transfected neuroblastoma cells upon application of low (picomolar) amounts of Ab or N-terminal Ab-peptides that are overlapping with the C-terminus of APPsa (Dougherty et al, 2003;Lawrence et al, 2014). Recently, low (picomolar) amounts of Ab were shown to increase synaptic vesicle recycling via a7-nAChRs signaling in hippocampal neurons (Lazarevic et al, 2017). Moreover, low amounts of Ab had been found to stimulate synaptic plasticity and memory in wild-type mice (Puzzo et al, 2011;Lawrence et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The enhancement of PTP by APPsa, as observed in our study, is consistent with previous studies that reported increased Ca 2+ influx in synaptoneurosomes and a7-nAChRs transfected neuroblastoma cells upon application of low (picomolar) amounts of Ab or N-terminal Ab-peptides that are overlapping with the C-terminus of APPsa (Dougherty et al, 2003;Lawrence et al, 2014). Recently, low (picomolar) amounts of Ab were shown to increase synaptic vesicle recycling via a7-nAChRs signaling in hippocampal neurons (Lazarevic et al, 2017). Moreover, low amounts of Ab had been found to stimulate synaptic plasticity and memory in wild-type mice (Puzzo et al, 2011;Lawrence et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…When applied to slices of cDKO mice, both APPsa and CTa16 enhanced, in a BTX-sensitive manner, the early phase of post-tetanic potentiation (PTP) during the first minutes after start of baseline recording, which is believed to involve Ca 2+ build up in presynaptic terminals. Recently, low (picomolar) amounts of Ab were shown to increase synaptic vesicle recycling via a7-nAChRs signaling in hippocampal neurons (Lazarevic et al, 2017). The enhancement of PTP by APPsa, as observed in our study, is consistent with previous studies that reported increased Ca 2+ influx in synaptoneurosomes and a7-nAChRs transfected neuroblastoma cells upon application of low (picomolar) amounts of Ab or N-terminal Ab-peptides that are overlapping with the C-terminus of APPsa (Dougherty et al, 2003;Lawrence et al, 2014).…”
Section: Of 23supporting
confidence: 92%
“…The increase in mEPSC frequency and the decrease in PPF suggest a presynaptic mechanism of neurotransmitter release, consistent with previous electrophysiological findings showing that pM oA␤ 42 affect basal synaptic transmission, inducing an increase of fiber volley amplitude, an index of presynaptic recruitment (Gulisano et al, 2018b), and posttetanic potentiation, a form of short-term plasticity due to presynaptic calcium entry (Puzzo et al, 2008). Furthermore, it has been recently demonstrated that A␤ exerts an opposite effect on synaptic vesicle recycling depending upon the dose (Lazarevic et al, 2017), consistent with other studies showing a sustained increase of mEPSC frequency after prolonged exposure to 200 pM oA␤ 42 (Koppensteiner et al, 2016) or treatment with inhibitors of A␤ degradation (Abramov et al, 2009). In these circumstances, high levels of A␤ may maintain neurotransmitter release for a longer period, leading to vesicle depletion (Parodi et al, 2010), or enter neurons directly, affecting presynaptic proteins such as synaptophysin, VAMP2, or synapsin I (Russell et al, 2012;Koppensteiner et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…memory depending upon its concentration (Puzzo et al, 2012;Gulisano et al, 2018b). Here, we first performed a DR curve to confirm that 200 pM oA␤ 42 was the dose capable of enhancing LTP, whereas 200 nM impaired it, consistent with previous works (Puzzo et al, 2008(Puzzo et al, , 2011(Puzzo et al, , 2012Garcia-Osta and Alberini, 2009;Morley et al, 2010;Lazarevic et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…At physiological (picomolar) concentrations, Aβ has been shown to positively regulate synaptic transmission by upregulating the presynaptic neurotransmitter release probability (Pr) [14][15] . Low to moderate levels of Aβ may augment Pr by increasing presynaptic Ca 2+ via presynaptic APP homodimerization, activating exocytotic Ca 2+ channels, and regulating presynaptic α7 nicotinic acetylcholine receptors [16][17] . In this study, pathological levels of Aβ obviously decreased the Ca 2+ oscillation and synaptic transmission (Figs.…”
Section: Discussonmentioning
confidence: 99%